Pengaruh Alokasi Dana Desa (ADD) dan Pendapatan Asli Desa (PADesa) Terhadap Kesejahteraan Masyarakat Desa Sukorejo - Hening Anitasari; Moh. Saiful Anam; Dados Susilowati; Happy Adianita (Departement of Mathematics Education, 2023)
This study aims to describe the effect of Village Allocation Funds (ADD) and Village Original Income (PADesa) on Village Community Welfare. The location of Sukorejo Village, Bojonegoro District, Bojonegoro Regency used a sample of 30 respondents. Sukorejo Village is the largest recipient of Village Fund Allocations, this is based on a reference to the high poverty rate of the population. This study uses WarpPls analysis to describe the data obtained from the location. In accordance with the results of the research and discussion that has been carried out, it can be concluded that the village's original income has an effect and is significant on the welfare of the community. So that the village's original income is still dominant in influencing the welfare of the people in Sukorejo Village. This research is limited to 3 variables which causes it to be known clearly which ones will have an effect.